Reentrant equilibrium disordering in nanoparticle–polymer mixtures - Dong Meng (Nature Portfolio, 2017)
Colloids: Polymers hold it together, for a while Polymers need to be the right length if they are to hold NPs into a crystal structure, shows research from scientists in the USA. Sanat Kumar from Columbia University and colleagues explain why small particles suspended in a solution, known as a colloid, become ordered then disordered when a polymer is added. The particles in a colloid are usually free to move around, but the addition of a polymer causes them to form a crystal-like structure. Adding more polymer returns the colloid to a disordered state. Kumar et al. use molecular dynamic simulations and density functional theory to show that this occurs because, while the crystal is stabilized at intermediate polymer density by polymer-induced nanoparticle attraction, it is destabilized at higher densities when the longer polymer chains can’t fit in the gaps between the particles.